Experimental Evaluation of Key Fermentation Variables Affecting Bioethanol Production - Adiya, Zainab Ibrahim S G; Abdullahi, Fodio; Umar, Ishaq; Bello, Safiya Zaki; Atiku, Farooq Abubakar; Mustafa, Bintu Grema (Indonesian Green Technology Journal, 2026)
The influence of process variables (temperature, agitation speed, and fermentation duration (hours)) during bioethanol production was evaluated with the aim of finding the optimal conditions of bioethanol production from groundnut shells and Saccharomyces cerevisiae yeast. Temperature was evaluated at 30, 35, and 40°C  for a 120-hour fermentation duration. The temperature of 35 gave the highest reducing sugar concentration (207mg/dL), bioethanol quantity (134mL), and yield (44.7%).  Agitation speed was assessed at 200, 400, and 600 rpm at 35°C, with a fermentation duration of 120 hours. It was found that as the agitation speed increases, the bioethanol quantity and percentage yield also increase in the order 200rpm < 400rpm < 600rpm. The fermentation duration was studied for 120, 240, and 360 hours at 35°C. It showed an opposite trend to that of agitation speed, whereby bioethanol quantity and percentage yield decrease with increasing fermentation duration in the order 120 hours > 240 hours > 360 hours. Based on the conditions investigated in this study, it was concluded that the optimal conditions for bioethanol production using groundnut shells as substrate and Saccharomyces cerevisiae yeast species are at a temperature of 35°C, an agitation speed of 600 rpm, and 120 hours of fermentation duration